Synthesis and functional properties of nanostructured Gd-doped WO3/TiO2 composites for sensing applications. (January 2020) - Mathankumar, G.; Bharathi, P.; Mohan, M. Krishna; Harish, S.; Navaneethan, M.; Archana, J.; Suresh, P.; Mani, G.K.; Dhivya, P.; Ponnusamy, S.; Muthamizhchelvan, C.
Abstract: Gd-doped WO3 and Gd-doped WO3 /TiO2 nanocomposites were synthesized using simple acid preparation and hydrothermal method. Gd-doped WO3 improves the sensing properties by creating more oxygen vacancy. The structural and morphological analysis confirms the formation of Gd-doped WO3 /TiO2 nanocomposites. By addition of TiO2 to various concentration of Gd-doped WO3, the change in morphology from disordered nanosheets to flake-like morphology was observed. The chemical composition of the samples were confirmed by XPS analysis. The elemental mapping confirms the presence of Gd, W, O and Ti elements in the nanocomposites. The optical studies confirmed the changes in bandgap with doping of Gd. The sensor sensitivity was found to be greatly influenced by addition of Gd in WO3 and WO3 /TiO2 and the high response was observed for 3% Gd-doped composites towards ammonia.